Rapports entre l’Homme et l’environnement dans le récit de Jacques Roumain : « Gouverneurs de la rosée » - Obrillant Damus (Études Caribéennes)
The narrative is, to some extent, a re-presentation of reality that the writer lived. Jacques Roumain has fictionalized the close relationship between man and his environment, which gives a universal dimension to the story. Environmental problems that have occurred in recent decades Haiti lead us to consider "Gouverneurs de la rosée" as a fiction-reality. From an analysis of linguistic and sociological nature, I showed how Manuel, the main character of the story, is taken to transform the mentality of the villagers. My thinking is based on the words of the narrator and most of the characters. This new reading of "Gouverneurs de la rosé" allowed me to argue that we can learn much from the ecological discourse involved in its construction. Even if it is fictional, this complex story can enlighten the minds of actual empirical beings.